Technical Analysis of a Proposed HVDC Transmission Line Between HassiMessaoud and El-Khroub in Algeria - Abdelghani Guechi; Nedjem-Eddine Benchouia; Mohammed Saaidia (IIETA, 2024)
Algeria will probably face great challenges in the energy sector in the near future due to the continuous increase in demand for electrical energy, old and insufficient local power stations and its dependence mainly on fossil energies. However, Algeria is considered as one of the most important countries in terms of solar energy potentials, especially in the center and south of the country, enabling it to address future energy challenges. Moreover, Algeria could become an important solar electrical energy exporter to African and even European countries. In this paper, we are interested by the electrical transmission network that could be suitable for the establishment of solar power plants in the Algerian desert. We propose the use of high-voltage direct current (HVDC) transmission technology based on a line-commutated converter (LCC) to connect one of the potential candidate region with huge potential for solar energy, namely Hassi-Messaoud region, to El-Khroub region as a central distribution node of electrical power at the Northeast of Algeria. A technical analysis of the proposed system is conducted and a comparison against high voltage alternating current (HVAC) transmission technology is performed to evaluate its suitability and effectiveness. The obtained results indicate that implementing a power transmission project via HVDC is technically feasible and suitable option.
Keywords: electricity transportation; HVDC electricity; environmental study; technical study; renewable energy